Effects of moderate electric fields (MEF) on denaturation of whey proteins solutions - Pereira, Ricardo (2012)
Electric fields application during thermal processing are now receiving increased attention due to uniform heating of liquids and extremely rapid heating rates, which presumably enables higher temperatures to be applied without inducing excessive denaturation of the constituent proteins [1]. The aim of this work was to evaluate the effects of moderate electric fields (MEF) on denaturation kinetics and thermodynamic properties of whey protein dispersions at temperatures ranging from 75 to 90 ºC. Application of MEF led to a lower denaturation of whey proteins, kinetically traduced by lower values of reaction order (n) and rate constant (k) (p < 0.05), when compared to those from conventional heating under equivalent heating rates and holding times. Furthermore, the application MEF combined with short come-up times has reduced considerably the denaturation of proteins during early stages of heating (>30% of native soluble protein than conventional heating). In general, denaturation reactions during MEF were less dependent on temperature increase presenting higher values of ΔG# in the range of temperatures studied. Further, MEF produced smaller changes (p < 0.05) in whey protein aggregates’ size when compared with a conventional heating MEF offers the potential to change the functional and technological properties of whey proteins, by changing their degree of denaturation. An accurate selection of the MEF process variables may allow controlling the size of protein nanoparticles. These findings could open novel perspectives on the use of OH not only in food and bioprocessing applications, but also in the pharmaceutical area.